Pengaruh Kompensasi Dan Komunikasi Interpersonal Terhadap Kinerja Karyawan Melalui Semangat Kerja - Maridha, Vricillia Jihan; Kustini, Kustini (Akuisisi : Jurnal Akuntansi, 2023)
This study aims to analyze the effect of the compensation model and interpersonal communication on the performance of CV Rizky Trans Jaya employees through morale. Work spirit which is still indicated to be low is a problem for CV Rizky Trans Jaya. The population in this study were all truck drivers who were employees of CV Rizky Jaya Trans and a sample of 36 people. This study uses the method of distributing questionnaires in the form of a questionnaire as a data collection method and using Smart PLS as a data analysis tool. The results of this study found that compensation has a positive but not significant effect on work morale, interpersonal communication has a positive and significant effect on work morale. compensation has a positive but not significant effect on employee performance, interpersonal communication has a positive and significant effect on employee performance, morale has a positive and significant effect on employee performance, compensation through morale has a positive but not significant effect on employee performance, interpersonal communication through work morale positive and significant effect on employee performance.